Village Forests: a Solution to the Legal Problems Involved in Joint Forest Management - Ahmad, Tasneem (Indian Forester, 2001)
With the object of resolving legal conflicts heing faced in day to day implementation of the Joint Forest Management programme, it has been suggested in the paper to invoke the provisions contained in Chapter III of Indian Forest Act, 1927 regarding formation of Village Forests. Such a measure would not only provide sound legal basis to the entire programme, but would also solve the problems related to the conflicts arising out of the exercise of numerous adverse rights of the people already existing in these forests.